Advancing the Measurement of Care Coordination in Pediatric Behavioral Health. Issue 8 (October 2016) - Jorina, Maria; Cammaerts, Ayesha; Singer, Janice; Ozonoff, Al; Chan, Eugenia; Antonelli, Richard; Gurvitz, Michelle; Jenkins, Kathy
Abstract: Objective: To describe the measure review and evaluation process used to identify new measures of care coordination for children with behavioral health needs conducted as part of Massachusetts' Children's Health Insurance Program Reauthorization Act Quality Demonstration Grant. Method: The Massachusetts Child Health Quality Coalition identified a shortage of pediatric measures of care coordination in behavioral health. After an extensive literature review, the Measure Development Committee applied the Care Coordination Key Elements Framework (Framework), which was designed as part of the grant work, and used a modified RAND Delphi method to conduct feasibility and validity evaluation and propose the new candidate measures for further rigorous testing. Results: Thirty-two measures were evaluated. One existing Healthcare Effectiveness Data and Information Set and 8 newly proposed measures met the criteria for feasibility and reliability. These measures represented each of the key elements contained in the Framework. The measures need further testing to ensure scientific acceptability and wide usability. Conclusion: A multipronged methodology was used to propose measures of care coordination in the space of pediatric behavioral health to fill the identified gaps in existing measures. Abstract : Supplemental Digital Content is Available in the Text.